A cohort study of low Apgar scores and cognitive outcomes. Issue 2 (4th October 2007) - Odd, D E; Rasmussen, F; Gunnell, D; Lewis, G; Whitelaw, A
Abstract : Objective: To investigate the association of brief (0–5 minutes) and prolonged (>5 minutes) low Apgar scores (<7) in non-encephalopathic infants with educational achievement at age 15–16 and intelligence quotients (IQs) at age 18. Design: Population-based record-linkage cohort study of 176 524 male infants born throughout Sweden between 1973 and 1976. Patients and methods: Data from the Medical Birth Register were linked to Population and Housing Censuses, conscription medical records (IQ), and school registers (summary school grade). Infants were classified according to the time for their Apgar score to reach 7 or above. Premature infants and those with encephalopathy were excluded. Results: Infants with brief (OR = 1.14 (1.03–1.27)) or prolonged (OR = 1.35 (1.07–1.69)) low Apgar scores were more likely to have a low IQ score. There was an increased risk of a low IQ score (p = 0.003) the longer it took the infant to achieve a normal Apgar score. There was no association between brief (OR = 0.96 (0.87–1.06)) or prolonged (OR = 1.01 (0.81–1.26)) low Apgar scores and a low summary school grade at age 15–16, or evidence for a trend in the risk of a low school grade (p = 0.61). The estimated proportion with an IQ score below 81 due to transiently low Apgar scores was only 0.7%. Conclusions: Infants in poor condition at birth have increased risk of poor functioning in cognitive tests in later life. This supports the idea of a "continuum of reproductive casualty", although the small individual effect suggests that these mild degrees of fetal compromise are not of clinical importance.